Evaluation of Fundus Function in Mature Cataract Patients by Visual Electrophysiology - Min Zhang; Min Ji; Mengjia Tan; Ying Yu; Huaijin Guan (Journal of Ophthalmology)
Purpose. To explore the value of visual electrophysiology in evaluating the fundus function of mature cataract patients. Methods. 124 mature cataract patients (153 eyes) were examined before cataract surgery; the examinations included best corrected visual acuity (BCVA), pattern visual evoked potential (PVEP), full-field electroretinogram (ffERG), and multifocal electroretinogram (mfERG). According to the postoperative fundus conditions, the subjects were divided into two groups: the no fundus disease group and the fundus disease group. Approximately one month after the operation, BCVA was measured, and visual electrophysiology was performed on subjects who had a stable fundus condition and had not received treatment for fundus disease. Results. One month after cataract surgery, BCVA ≤ 0.3 logMAR was found in 60 eyes (96.8%) without fundus disease and 59 eyes (64.8%) with fundus disease. Compared with the group without fundus disease, the preoperative electrophysiological examination of the group with fundus disease showed that the amplitude of ffERG waves and the amplitude density of the P1 wave in the 2nd to 5th rings of mfERG were decreased (all P < 0.05). ffERG and mfERG can be used for differential diagnosis of fundus disease (all P < 0.05), while PVEP has no significant diagnostic value for fundus disease (all P > 0.05). In the group without fundus disease, the amplitude of the PVEP 15′ P100 wave and the amplitude of dark-adapted (DA) 0.01 b-wave, DA 3.0 a-wave, and DA 10.0 a-wave were negatively correlated with postoperative logMAR BCVA (all P < 0.05). In the group with fundus disease, the amplitude of PVEP and ffERG and the amplitude density of mfERG were negatively correlated with postoperative logMAR BCVA (all P < 0.05). In the eyes of cortical cataracts, some parameters of PVEP, ffERG, and mfERG were significantly different before and after surgery. In the eyes of nuclear cataracts, some parameters of ffERG and mfERG were significantly different before and after surgery. In the eyes of posterior subcapsular cataracts, some parameters of PVEP and ffERG were significantly different before and after surgery. Conclusions. ffERG and mfERG can be used to detect fundus disease in mature cataract patients. The preoperative visual electrophysiological examination has high clinical value in predicting postoperative vision of mature cataract patients with fundus disease. Different types of cataracts have different effects on electrophysiological examination results. When interpreting the electrophysiological report, it is necessary to consider the existence of cataracts. This trial is registered with 2019-K068.